Efficiency in real estate development: Is management or robotics the key? - Liu, Yuming; Hizami bin Alias, Aidi; Azam Haron, Nuzul; Abu Bakar, Nabilah; Wang, Hao (National Cheng Kung University, 2024)
This study examines the impact of construction robotics (CR) and agile project management (APM) principles on operational efficiency in Chinese commercial residential projects (CRPs). By analyzing 107 CRPs across 21 provinces, including 30 using CR technology, we employ a novel methodology that combines superefficiency SBM-DEA, APM frameworks, and Tobit regression models. The results show that CR implementation improved work efficiency by 2.59% on average. Operational efficiency varied regionally, with the eastern area (mean 0.3963) outperforming the central (0.3651) and western (0.3790) areas. The provinces of Jiangsu and Shanghai demonstrated the highest efficiencies. APM factors significantly influence efficiency: top management commitment negatively (−0.9432) and product owner involvement positively (0.2266). CR implementation in the main structural phase showed the strongest positive correlation (0.0438). Three of the nine typical CR technologies on the project duration's critical path were the most popular among the contractors. The study identified potential improvements in interim payments and inventory balance efficiency. The findings extend APM theory to real estate development, refine technology adoption models in construction, and reveal tensions between contractor priorities and overall project efficiency. Practical implications include recommendations for targeted CR implementation, management restructuring, and policy support. Future research should explore longitudinal effects, broader geographic scopes, and potential mediating variables in CR and APM dynamics in real estate development.